Clostridium caldaquaticum sp. nov., a thermophilic bacterium isolated from a hot spring sediment. Issue 1 (11th January 2023) - Lv, Ai-Ping; Ming, Yu-Zhen; Liu, Ze-Tao; Ouyang, Yu-Ting; Li, Meng-Meng; Lian, Zheng-Han; Jiao, Jian-Yu; She, Ting-Ting; Liu, Lan; Li, Wen-Jun
Abstract : A novel anaerobic bacterium, designated SYSU GA19001 T, was isolated from a hot spring sediment sample. Phylogenetic analysis indicated that the isolate belongs to the genus Clostridium, and showed the highest sequence similarity to Clostridium swellfunianum CICC 10730 T (96.63 %) and Clostridium prolinivorans PYR-10 T (96.11 %). Cells of strain SYSU GA19001 T were Gram-stain-positive, spore-forming, rod-shaped (0.6–0.8×2.6–4.0 µm) and motile. Growth was observed at pH 5.0–9.0 (optimum, pH 7.0), 37–55 °C (optimum, 45 °C) and in NaCl concentrations of 0–2.0 % (optimum, 0 %). The genomic DNA G+C content was 31.62 %. The major cellular fatty acids of strain SYSU GA19001 T were C14 : 0, iso-C15 : 0, C16 : 0 and summed feature 8. The prominent polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol. Meso -diaminopimelic acid was the diamino acid in peptidoglycan. Based on the results of phylogenetic, chemotaxonomic and phenotypic analyses, strain SYSU GA19001 T represents a novel species of the genus Clostridium, for which the name Clostridium caldaquaticum sp. nov. is proposed. The type strain of the proposed novel species is SYSU GA19001 T (=NBRC 115040 T = CGMCC 1.17864 T ).